Pelatihan Sistem Informasi Pelayanan Surat Pengantar Untuk Perangkat Desa Mangunjaya Kecamatan Tambun Selatan Kabupaten Bekasi - Mayadi Mayadi; Prio Kustanto (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
Abstract   Utilization of information and communication technology is applied to help facilitate human work and make it easier to get information. Utilization of information technology for government agencies is a useful tool to improve services to the community. Mangunjaya Village is a government agency at the village level that directly provides services to the community. The services provided include making cover letters, such as Identity Cards (KTP), Family Cards (KK) and Birth Certificates. With the help of information system technology, the Cover Letter service for the Mangunjaya Village Apparatus, Tambun Selatan District, is expected to help the community service so that it can be relatively more optimal and faster. This activity, which was held in Mangunjaya Village, out of a total of 30 participants who expressed satisfaction with the seminar held in Mangunjaya Village, as many as 57% were very satisfied, 30% satisfied and 13% said they were quite satisfied with the presentation delivered by the speaker.   Keywords: Information, Information System, Letter, Service, System   Abstrak   Pemanfaatan teknologi informasi dan komunikasi diterapkan untuk membantu memudahkan pekerjaan manusia dan mempermudah mendapatkan informasi. Pemanfaatan teknologi informasi bagi instansi pemerintah merupakan alat bantu yang berguna untuk meningkatkan pelayanan kepada masyarakat. Desa Mangunjaya merupakan instansi pemerintah pada tingkat desa yang langsung melakukan pelayanan kepada masyarakat. Pelayanan yang diberikan diantaranya adalah pembuatan surat pengantar, seperti Kartu Tanda Penduduk (KTP), Kartu Keluarga (KK) dan Akta Kelahiran. Dengan bantuan teknologi sistem Informasi pelayanan Surat Pengantar untuk Perangkat Desa Mangunjaya Kecamatan Tambun Selatan diharapkan dapat membantu pelayanan masyarakat hingga dapat relatif lebih optimal dan cepat. Kegiatan yang diselenggarakan di Desa Mangunjaya ini dari total 30 peserta yang menyatakan kepuasan terhadap seminar yang dilakukan di Desa Mangunjaya, sebanyak 57 % sangat puas, 30 % puas dan 13 % menyatakan cukup puas dengan pemaparan yang disampaikan oleh pembicara.   Kata kunci: Informasi, Sistem Informasi, Pelayanan, Surat, Sistem